(untitled) (Research, Society and Development, 2020)
Mimosa caesalpiniifolia is a leguminous tree native and endemic to Brazil with geographic distribution in the Caatinga, Cerrado, Amazon and Atlantic Forest. Its most popular name is Sabiá. The species is commonly used in programs for the recovery of degraded areas, the construction of hedges, the manufacture of posts and fence posts, the formation of energy forests, the production of forage, in addition to being meliferous, ornamental and used in traditional medicine, therefore, has multiple uses. However, the species is vulnerable to attacks by the beetle Oncideres ocularis, belonging to the coleoptera order. It is fast to reproduce and is responsible for preventing the healthy development of seedlings and trees, preventing its use for various purposes. Thus, it becomes necessary to adopt an integrated pest management, through its constant monitoring and the use of mechanical and physical control techniques. Thus, the objective was to carry out a bibliographic review on the management of Oncideres ocularis in Mimosa caesalpiniifolia.